Knowledge of sociology of development applied to nursing practice by registered nurses in public training hospitals in Namibia - Shikongo, Katriina Kuna I. (International Journal of Advanced Nursing Studies, 2014)
Background: Nurses trained at the University of Namibia are exposed to social studies on basis of the fact that their career or profession is also social of nature. It was found to be a necessity to derive knowledge from social sciences one of which is Sociology of Development. The nurses in their endeavors to care for their patients and attend to their clients act in the sphere of development taking place in the society which affects their own functions and behaviors as well as those of their patients. Aim: The aim was to determine and describe how the nurses integrate and transfer knowledge from Sociology of development to their clinical practice. Method: A quantitative design employed with the questionnaire as tool for collecting data. A statistical descriptive analysis testing the relationship between the personal/biographical data, as independent variables, and specific answers on issues of development as dependent variables was used. The responses were based on an ordinal scale of 1 – 5, with 1= not at all, and 5 = to a large extent, while the cross at 3 indicated that the specific item is practical. Result: The results have indicated no statistical significant differences in most of these variables but with general trends on some of the cases like the extent to which registered nurses give assistance to women deprived of their rights, empowerment of women in the community and observation of women subjected to domestic violence. The average score between the two groups on the dependent variables have also reflected a trend of being less than 3 (¯x < 3.00) on the five point scale. Conclusion: The results indicated that registered nurses differ with regard to the extent to which they relate knowledge from Sociology of Development to nursing practice and their reflection of knowledge is in those three items below the expected average of being considered as making impacts. Keywords: Integration; Knowledge; Nursing Practice; Reflection; Registered Nurses; Sociology of Development.